PENGARUH AUDIT TENURE, SPESIALISASI KANTOR AKUNTAN PUBLIK DAN UKURAN PERUSAHAAN TERHADAP TERHADAP KUALITAS AUDIT - Nugrahanti, Yavina; Darsono, Darsono (Diponegoro Journal of Accounting, 2014)
This study aims to analyze and provide empirical evidence of the influence of audit tenure, specialization of audit firm, firm size to audit quality. Audit quality is measured by earnings surprise benchmark. This  approach was  adopted by Rossieta  and  Wibowo  from  one  of  Carey  and  Simnett  audit  quality  analysis models. Hypothesis (1) Audit tenure positively affect to the audit quality, (2) Specialization of audit firm positively affect to the audit quality, (3) Firm Size positively affect to the audit quality.The research used 273 manufacturing companies listed on Bursa Efek Indonesia (BEI) from 2010 – 2012.Determination of the sample using purposive sampling method. Data from this study were obtained from financial statements of manufacturing firms drawn from the Indonesia Stock Exchange and Indonesian Capital Market Directory. To analyze the effect of independent variable on the dependent variable, data were analyzed by logistic regression analysis.The result shows that audit tenure and industry specialization of audit firm have positive and significant effect to the audit quality, and firm size doesn’t has significant effect to the audit quality.